The Space Rush: Reviewing Indonesia’s Space Law in Facing the Rise of Space Mining - Suryaatmadja, Shannon; Sacharissa, Vicia; Tedemaking, Konrardus Elias Liat (Faculty of Law, Hasanuddin University, 2020)
Space technology development shows feasibility of actualizing future space mining. There are numerous efforts to utilize resources from celestial bodies; whether as fuel, an alternative source for scarce minerals, or as an in-situ support for future human habitation in outer space. This article identifies potential clashes between ongoing space mining practices and the interests of developing nations. The main concern is accessibility: will the race to dominate space mining leave no room for non-space faring nations to utilize space resources, or even access potential space mining locations? The current international space law has several loopholes such as the absence of provisions regarding ownership of space resources, and the lack of inclusion of private actors, especially considering their role in furthering the space mining industry. This article also examines Indonesia’s regulation on space activities, including mining and provide recommendations. Current regulations imply there is a vision for Indonesia to be a large space actor in the future, but no instrument puts specific focus as of yet to space mining. Lack of dedicated funding and technology also exist, but there are various opportunities to attain this, provided Indonesia is able to utilize them for national interests.